A case study on electrical and electronics system of a car -Proton Perdana E55A- SOHC / Syaifudin Ngah and Ahmad Sukri Ibrahim - Ngah, Syaifudin; Ibrahim, Ahmad Sukri (2001)
This study case of electric and electronic system of a car is done by selecting our nation's produced car, the Proton Perdana E55A 4G63 - SOHC (1997). We start doing this study by listing the topics should be covered by us with help from our study case advisor, Dr Abdul Rahim Bin Atan .We have discussed that we are going to do it thoroughly and at the same time try to understand the requirement needed for this project. -Our advisor has guided us to SAGA ACADEMY .Then the head instructor had helped us in giving numerous data and diagram for our references. We had a WORKSHOP MANUAL IN ELECRICAL WIRING for Proton Perdana. Next we learned how to read wiring diagram s, wiring harnesses and circuit diagrams. The manual is very detail and we have to select important point from it. We started to discuss the project during our free time and divided jobs between us. Everyone in this group have played a good role in this study project. The cooperation between us is good we live together in a house. Even our advisor lives near to our resident and it's easy to talk and discuss with him. The last portion of the project is typing and editing the data and points. We refer a study case in another project and begin to work on it. The use of information technology is used too in this project. A full set of multimedia computer with printer, scanner plus a modem for the use of printing, scanning and surfing for data, pictures and information in the web. Finally the study case project has been done and we have experienced some good value and gained knowledge through this project. We hope this project be a guide for our fellow friend in both mechanical engineering and UiTM student.